2002
DOI: 10.1007/s11920-002-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on smoking cessation among substance abusers

Abstract: The prevalence of nicotine dependence among alcohol or other substance abusers is extremely high, and surveys have revealed that many patients in drug or alcohol treatment programs are interested in smoking cessation. However, smoking cessation has not been a traditional focus in clinical interventions for this population. Recent evidence from clinical trials among individuals abusing alcohol, marijuana, cocaine, or opioids have shown the following: 1) smokers with a past but not current history of alcohol dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…50 Furthermore, given the high prevalence of drug use in many primary care populations 22,40,50,51 the efficacy of alcohol and tobacco interventions could be compromised if providers are unaware of comorbid drug use. 52,53 Having information about a patient's drug use can thus assist the clinician in carrying out activities that are integral to the quality and safety of the medical care they provide, including safer prescribing, making correct diagnoses, identifying common comorbidities, and engaging patients in management of their other medical conditions. 54 …”
Section: Discussionmentioning
confidence: 99%
“…50 Furthermore, given the high prevalence of drug use in many primary care populations 22,40,50,51 the efficacy of alcohol and tobacco interventions could be compromised if providers are unaware of comorbid drug use. 52,53 Having information about a patient's drug use can thus assist the clinician in carrying out activities that are integral to the quality and safety of the medical care they provide, including safer prescribing, making correct diagnoses, identifying common comorbidities, and engaging patients in management of their other medical conditions. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Smoking Prevalence in Addiction Treatment: A Review 2009), with many studies reporting ranges of 75%-90% (Gorelick, Simmons, Carriero, & Tashkin, 1997;Kalman, 1998;Kozlowski et al, 1989;Lai, Lai, Page, & McCoy, 2000;Patkar, Sterling, Leone, Lundy, & Weinstein, 2002;Sees & Clark, 1993;Sullivan & Covey, 2002). Papers reporting these estimates often rely on two or three other papers, and there is at present no systematic review of papers reporting smoking prevalence among those in addiction treatment.…”
Section: Reviewmentioning
confidence: 99%
“…Studies ( Humfl eet, Munoz, Sees, Reus, & Hall, 1999 ;Sullivan & Covey, 2002 ;Torchalla et al, 2011 ) in other populations have shown that these comorbidities make quitting smoking more challenging. However, there are currently no data about the effects of these comorbidities on smoking cessation in homeless populations.…”
Section: Nicotine and Tobacco Researchmentioning
confidence: 99%